The Development of Student Worksheets Based Discovery Learning on Excretion System Materials to Improve Scientific Literacy Skills for Senior High School Students - Putri, Puspa Regina; Marianti, Aditya (Journal of Biology Education, 2021)
This study aims to analyze the feasibility, practicality, and effectiveness of the student worksheet based on discovery learning on excretory system material to improve the scientific literacy skills of senior high school students. The research was conducted at Senior High School 1 Banjarnegara with a sample of 70 students of XI MIPA class. The type of this study is Research & Development. The data collection technique used in this study is the interview method, the questionnaire method, and the pretest and posttest test methods. The data analysis techniques used is descriptive, percentage descriptive and quantitative descriptive techniques. The results showed that student worksheet based discovery learning on excretory system materials were very feasible to use with the results of the percentage of material expert validity tests is 94.79% and the percentage of media experts validity tests is 84.72%. Student worksheet based discovery learning on excretory system materials are also categorized as practical to use with an average percentage of practicality test by teachers is 87% and an average percentage of practicality test by students is 93.7%. Then the results of the N-Gain data pretest and posttest as many as 83% of students completed obtaining an increase in moderate to high scale scientific literacy. Based on these results, it can be concluded that the student worksheet based discovery learning on excretory system materials is valid and practical to use in learning and effective in improving scientific literacy of high school students.